2020
DOI: 10.1002/chem.202002327
|View full text |Cite
|
Sign up to set email alerts
|

Chemists around the World, Take Your Part in the Circular Economy!

Abstract: Based on recent examples and initiatives reported in the literature, this concept article discussesh ow chemistry can contribute to the circulare conomy approach in order to improve our current and future economical, societal, and environmental system. Through five proposed levelso fc ontribution, chemists can take as ignificant part in this globala pproach via the consideration of green chemistry principles, the simplificationo fs yntheses, the limitation of complex products preparation, the efficient utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This achievement provides significant benefits in terms of sustainability to the manufacturing process of advanced materials based on reduced energy consumption and lower CO 2 emissions contributing to a greener worldwide economy. [ 21 ] Additionally, the method can in principle be applied to other materials based on metal oxides, demonstrating the general validity of the self‐induced solution seeding approach. Preliminary results have shown that the minimum crystallization temperatures of Bi 4 Ti 3 O 12 and LaFeO 3 thin films prepared by this solvent‐engineering strategy are effectively reduced in the course toward reaching the equilibrium from the initial solution mixture of precursors ( t 0 ) to the self‐induced seeding solution ( t 7 ) (see Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…This achievement provides significant benefits in terms of sustainability to the manufacturing process of advanced materials based on reduced energy consumption and lower CO 2 emissions contributing to a greener worldwide economy. [ 21 ] Additionally, the method can in principle be applied to other materials based on metal oxides, demonstrating the general validity of the self‐induced solution seeding approach. Preliminary results have shown that the minimum crystallization temperatures of Bi 4 Ti 3 O 12 and LaFeO 3 thin films prepared by this solvent‐engineering strategy are effectively reduced in the course toward reaching the equilibrium from the initial solution mixture of precursors ( t 0 ) to the self‐induced seeding solution ( t 7 ) (see Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…In a concept article recently published in Chemistry -An European Journal, I discussed how chemistry can contribute to the circular economy approach to improve our environmental, economic and societal system. [4] Through five proposed levels of contribution (Figure 1), chemists can take their part in this adventure: 1 -innovation through the consideration of green chemistry principles, 2 -the simplification of syntheses, 3 -development of new technological systems and novel ways of valorization, 4 -systematic and generalized environmental and economic assessment, 5 -global approach in link with other actors and disciplines. This last level encourages chemists to work even more together across all fields of chemistry to find complementary solutions, but also to contribute more broadly by adopting territorial, multi-partners and multidisciplinary approaches within circular economy projects to ensure positive overall impacts.…”
Section: Levels Of Contribution Of Chemistry To Circular Economymentioning
confidence: 99%
“…The global increasing demand for alternatives to petroleum-based fuels and chemicals has recently emphasised the stringent need to also diversify and valorise the biobased waste with circular economy strategies [8,9]. Forestry and agricultural crop waste as well as by-products from food processing represent an abundant source of different components for further valorisation.…”
Section: Introductionmentioning
confidence: 99%